Application of the Environmental Fragility Index (EFI) inthe Integrated Terrain Geoaptitude (GEOINT) as a Tool forEnvironmental Land-Use Planning in Rural Areas of theAtenas Canton, Costa Rica - Ramírez Granados, Pablo Ignacio (2026)
This study presents the application of the Environmental Fragility Index for the geoaptitude variable in rural areas of the Atenas canton, province of Alajuela, Costa Rica. Cabinet information was collected and primary information was processed, as well aslocal studies that allowed categorizing the geological and geomorphological maps and establishing values to calculate geoaptitude. Hydrogeological information, slope stabil-ity and natural hazards were integrated into the geological and geomorphological maps using map algebra in a geographic information system (GIS) for zoning and the creationof categorized areas of environmental fragility. The methodology applied through GIS produced five maps categorized according to lithopetrophysical factors, external geodynamics, slope stability, hydrogeology and natural hazards. Each of these maps shows the relationship of the geoaptitude characteristics with their geographic location andtheir percentage weight. The five sub-factors were analyzed in relation to current land uses, and through an arithmetic process were integrated to form the integrated geoaptitude. The environmental fragility index based on geoaptitude allowed the zoning of the territory, identifying areas with technical limitations and areas with potential fordifferent degrees of current and future occupation.